1994
DOI: 10.1901/jeab.1994.61-479
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Chlordiazepoxide and Cocaine on Concurrent Food and Avoidance‐of‐timeout Schedules

Abstract: Five rats were trained on a concurrent schedule in which responses on one lever produced a food pellet on a random-interval 30-s schedule during 10 s of food availability associated with distinctive exteroceptive stimuli. Responses on another lever postponed for 20 s the presentation of a 50-s timeout, during which all stimuli were extinguished and the schedule contingencies on the food lever were suspended. The response rates maintained by the random-interval schedule exceeded those maintained by the avoidanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

1998
1998
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 28 publications
1
2
0
Order By: Relevance
“…Consistent with prior findings, the present results showed that responding can be maintained by postponing timeouts from a schedule of food delivery (D'Andrea, 1971;Ferster, 1958;Galbicka & Branch, 1983;Thomas, 1964Thomas, , 1965aThomas, , 1965bvan Haaren & Zarcone, 1994). In past studies, the effects of timeoutpostponement contingencies have been confounded with increases in the frequency of food reinforcement-an inevitable result of increased access to the reinforcement schedule available during time-in periods.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Consistent with prior findings, the present results showed that responding can be maintained by postponing timeouts from a schedule of food delivery (D'Andrea, 1971;Ferster, 1958;Galbicka & Branch, 1983;Thomas, 1964Thomas, , 1965aThomas, , 1965bvan Haaren & Zarcone, 1994). In past studies, the effects of timeoutpostponement contingencies have been confounded with increases in the frequency of food reinforcement-an inevitable result of increased access to the reinforcement schedule available during time-in periods.…”
Section: Discussionsupporting
confidence: 89%
“…One way to determine whether an event is aversive is to examine whether its termination or postponement will support responding. Indeed, some of the clearest evidence favoring a view of timeouts as aversive emerges from studies of timeout avoidance, in which responding is maintained by the postponement or cancellation of timeout from a schedule of positive reinforcement (D'Andrea, 1971;Ferster, 1958;Galbicka & Branch, 1983;Hackenberg, 1992;Morse & Herrnstein, 1956;Thomas, 1964Thomas, , 1965aThomas, , 1965bvan Haaren & Zarcone, 1994;Zimmerman, 1963).…”
mentioning
confidence: 99%
“…In basic research on aversive control, shock is a commonly used stimulus and it often serves as a reference stimulus when assessing the aversive function of other stimuli. Much research supports the notion that timeout functions in a comparable manner as shock when studied under similar experimental arrangements (DeFulio & Hackenberg, 2007; Kaufman & Baron, 1968; McMillan, 1967; Richardson & Baron, 2008; Thomas, 1965; but see exceptions in pharmacological studies reported by Branch et al, 1977, van Haaren & Anderson, 1998, and van Haaren & Zarcone, 1994).…”
Section: Methodsmentioning
confidence: 77%